Exploring Association of Anemia with Diabetic Foot Ulcer and its Impact on Disease Outcome in a Tertiary Care Hospital - Dur-E-Sameen, Muddasar Shahzad, Shahid Khan, Kamran Hakeem Khan, Sheikh Muhammad Ibqar Azeem, Zahid Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Both short-term and long-term complications are common in people with diabetes, making the disease quite difficult to manage. Among them development of foot ulcer is like a nightmare for diabetic patients. Foot deformities, impairment of microcirculation and concomitant neuropathy all add in the development of these ulcers, that are either delayed to heal or do not heal at all leading to amputation or in extreme cases even death. In addition to these major contributors, concomitant comorbidities like anemia may lead to development of an ulcer or effect it’s healing. If anemia identified and treated promptly may enhanced recovery of diabetic foot ulcer patients. We analyzed the effects of anemia on the prognosis of individuals with diabetic foot ulcers (DFUs). Methods: We prospectively followed 165 diabetic patients admitted to the hospital with DFU until they were either discharged or died. Patient's demographic data, characteristics of the ulcers, duration of diabetes, presence of comorbid conditions, need for blood transfusion and diabetic complications were all taken into account. The appropriate imaging and laboratory tests were conducted. The incidence of anemia and its effect on illness outcome in DFU patients were examined. Results: Anemia was found in 70% of patients with 38% required blood transfusion. The presence of gangrene, PAD, and an ulcer that had been present for more than a month prior to admission were all significant demographic and clinical predictors of anemia, [p0.008], [p0.00.1], [p0.001] respectively. Comorbidities like proteinuria [p0.003], moderate [p0.002] and severe [p0.00.1] constriction of the blood vessels, previous stroke [p0.012], kidney dysfunction [p0.002] were all significantly linked with anemia. Regarding effect of anemia on disease outcome delayed wound healing [p0.008], osteomyelitis [p0.005], amputation [p0.034] and mortality [p0.008] were all substantially correlated with anemia. Conclusion: Anemia was seen in majority of patients with DFU. Significant association was found between anemia and worse ulcer outcome in the form of delayed wound healing, osteomyelitis, mputation and mortality. Therefore, it needs to be identified and managed promptly, like other major risk factors such as infection, ischemia and pressure offloading, to promote earlier and complete healing. Keywords: Exploring, Association , Anemia, Diabetic Foot Ulcer , A Tertiary Care Hospital